Antifungal activity of oils macerates of North Sardinia plants against Candida species isolated from clinical patients with candidiasis. Issue 22 (16th November 2020) - Donadu, M.G.; Usai, D.; Marchetti, M.; Usai, M.; Mazzarello, V.; Molicotti, P.; Montesu, M.A.; Delogu, G.; Zanetti, S.
Abstract: Antibiotic resistance is one of the bigger problem of public health: the rise of multi-drug resistant organisms causes a challenge in the treatment of infective diseases. Anti-Candida resistance to conventional antifungal agents has increased in the last period. Our research was intended to evaluate antimicrobial activity of oil macerate (OM) of Helichrysum microphyllum Cambess. subsp . tyrrhenicum Bacch., Brullo & Giusso and OM of Hypericum perforatum subsp. angustifolium against several clinical strains. The study included 30 patients with candidiasis who had not received any antifungal treatment before they were enrolled. A collection of 30 clinical isolates belonging to 5 different species of Candida spp. was selected for this study. The data obtained showed an interesting activity of both Oil Macerate especially against C. krusei and C. parapsilosis . On the contrary, H. microphyllum Oil Macerate has had a better activity than the H.perforatum especially in relation to C. glabrata and C. krusei . Graphical Abstract: